2019
DOI: 10.1007/s42770-019-00043-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of biochar and PGPR consortia for sustainable production of wheat under semiarid conditions with a reduced dose of synthetic fertilizer

Abstract: This study investigates the combined effect of locally adopted plant growth promoting rhizobacteria (PGPR), biochar, and synthetic fertilizer on the wheat crop for the production and economic returns. A total of 20 PGPR strains were isolated from three different ecological zones of Pakistan and were evaluated. Of them, three isolates were selected for further studies. The treatments included (i) control with a full dose of the recommended fertilizer, (ii) control with half a dose of the fertilizer, (iii) PGPR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 38 publications
5
28
1
4
Order By: Relevance
“…Application of biochar to the soil is considered a practical approach to decrease soil moisture content because of its properties to get better soil hydrological parameters [ 39 ], which in turn enrich plant physiological and biochemical responses. It was of merit to perceive that biochar and SA coupled application had the uppermost intrinsic water use efficiency (WUEi) under water limiting condition in saline sodic soil [ 40 ]. The impact of biochar to avoid water deficit and soil salinity has been well documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of biochar to the soil is considered a practical approach to decrease soil moisture content because of its properties to get better soil hydrological parameters [ 39 ], which in turn enrich plant physiological and biochemical responses. It was of merit to perceive that biochar and SA coupled application had the uppermost intrinsic water use efficiency (WUEi) under water limiting condition in saline sodic soil [ 40 ]. The impact of biochar to avoid water deficit and soil salinity has been well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Singular biochar treatment could decrease the soil bulk density and increase soil surface area owing to its porous structure, leading to increasing the capability to uptake and hold water [ 38 ]. Furthermore, [ 40 ] affirmed that biochar possibly increases soil aggregate stability and therefore increases soil water holding under water deficit. Likewise, [ 39 ] demonstrated that the biochar porous structure declined evapotranspiration and augmented aeration and soil water retention as well as diluted ions concentration under saline soil, thus stimulate an appropriate soil for crop development.…”
Section: Discussionmentioning
confidence: 99%
“…Biochar is a carbon-rich organic additive and having manifold benefits for soil such as reduced nutrient leaching, better soil physical, and chemical and microbiological properties in contaminated soils (Dzvene et al 2019;Ijaz et al 2019) enhances CEC by improving soil health. Biochar has found to be a viable approach to drought soils due to its properties to improve soil hydrological properties (Omondi et al 2016;Yu et al 2017) which in return improve plant physiological and biochemical response.…”
Section: Discussionmentioning
confidence: 99%
“…co-inoculated in paddy rice (García de Salamone et al 2012). Ijaz et al (2019Ijaz et al ( , 2020 propose the use of PGPR consortia and biochar with reduced synthetic fertilization for maximizing wheat and peanut crop production as eco-friendly alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the above scenario, the use of plant growthpromoting rhizobacteria (PGPR) in agriculture could be a sustainable and environmentally friendly solution for crop fertilization by reducing the negative impact associated with the excessive use of chemical fertilizers (Glick 2014;Ijaz et al 2019Ijaz et al , 2020. PGPR exert a beneficial effect on plant growth through direct and indirect mechanisms.…”
Section: Introductionmentioning
confidence: 99%